Worldwide epidemiology of foot and ankle injuries during military training: a systematic review. Issue 2 (9th November 2020) - Fenn, Brian P.; Song, J; Casey, J; Waryasz, G R; DiGiovanni, C W; Lubberts, B; Guss, D
Abstract : Introduction: Musculoskeletal foot and ankle injuries are commonly experienced by soldiers during military training. We performed a systematic review to assess epidemiological patterns of foot and ankle injuries occurring during military training. Methods: A review of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search, done on 14 February 2019, resulted in 1603 reports on PubMed, 565 on Embase and 3 on the Cochrane Library. After reading the remaining full-text articles, we included 91 studies. Results: Among a population of 8 092 281 soldiers from 15 countries, 788 469 (9.74%) foot and ankle injuries were recorded. Among the 49 studies that reported on length of training, there were 36 770/295 040 (18.17%) injuries recorded among women and 248 660/1 501 672 (16.56%) injuries recorded among men over a pooled mean (±SD) training period of 4.51±2.34 months. Ankle injuries were roughly 7 times more common than foot injuries, and acute injuries were roughly 24 times more common than non-acute injuries. Our findings indicated that, during a 3-month training period, soldiers have a 3.14% chance of sustaining a foot and ankle injury. The incidence of foot or ankle injury during military parachutist training was 3.1 injuries per thousand jumps. Conclusions: Our findings provide an overview of epidemiological patterns of foot and ankle injuries during military training. These data can be used to compare incidence rates of foot and ankle injuries due to acute or non-acute mechanisms during training. Cost-effective methods of preventing acute ankle injuries and non-acute foot injuries are needed to address this problem.